In memoriam Dr. Olev Lugus (12.03.1935-27.06.2014). Mit Zusammenfassung - Laur, Anton (Estonian Discussions on Economic Policy, 2016)
Olev Lugus was born in a farmer’s family in the Sangaste Parish, Valga County on the 12th of March 1935. He began his education in the Restu primary school and continued in Valga Accounting and Planning Technical High School. After graduating from the Technical High School, he started his working career as an economist in the industry department at the Planning Committee of the Pärnu region. In 1953, his career continued in the Pärnu woodworking factory „Viisnurk“ in the position of senior engineer, later as a head of department. In parallel with work, Olev Lugus went to study at the Tartu State University, from which he graduated in 1962 in the speciality of industrial economics. After graduating, he decided to take up an academic career in economics. In 1962, he started his long and productive research career at the Institute of Economics, Academy of Sciences of the Estonian SSR (later Estonian Institute of Economics at Tallinn University of Technology); at first as a junior researcher, then, after post-graduate studies and defending the thesis of a Candidate of Economics (PhD)„The Main Perspectives and Economic Efficiency of the Complex Using of Wood in the Estonian SSR“ as a senior researcher (1971). Quite soon, in 1972, he was appointed a head of the department of industrial economics. In 1986, he was promoted to the position of research director and in 1989, was elected a director of the Institute of Economics. He remained the director of the Institute also after re-elections until 1998. In the period 1998–2000, he worked as an economic advisor to the Estonian Employers’ Confederation.Olev Lugus was the director of the Institute of Economics in a complicated but also a very interesting and promising period when Estonia regained its independence. It was not easy to be part of the process of reforming the Estonian Academy of Sciences and the research system. At the same time, it was very stimulating to take new challenges – important orders from new institutions of the Republic of Estonia for applied research and analyses. One of the new challenges was the launch of applications for international research projects. Under the leadership of Olev Lugus, the Institute of Economics faced these challenges successfully. The main area of his personal research was analysis and prognostication of development of the Estonian industry, focusing on analysis of the use of Estonian forest resources and wood industry. In the period of regaining independence in Estonia, different macro-economic research topics were on the agenda.Olev Lugus was the Estonian leader in 10 international projects, including with such partners as PHARE programme, International Centre of Economic Growth (ICEG, USA), Finnish Institute of Economic Research (ETLA) etc. He was also one of the leaders of working out the programme of Estonian economic independence (so-called IME-project). Olev Lugus was the Estonian coordinator of the ICEG (1985–1998); a member of the Estonian President’s Academic Council (1994–1996); a vice-chairman of the Estonian Economic Association and had several other important public appointments.He made over 2100 presentations in Estonia and abroad about his research findings and development problems of the Estonian economy. He was also an author of nearly 150 publications and an editor of 8 collections of research papers on economics, including the Estonian-Finnish joint collection “Comparison of the Estonian and Finnish Socioeconomic Development” (Helsinki 1993), which in 1994 received the Estonian Science Award in humanities and social sciences. Olev Lugus has been awarded a Badge of Honour Order (1981) and in 1987, he received the honorary title of the meritorious cultural figure of the Estonian SSR.Colleagues remember Olev Lugus as an energetic, productive and capable scientist who achieved a lot. He was a warm and friendly person, very considerate and kind to his colleagues. Olev Lugus, an internationally renowned Estonian economist and tireless populariser of economics died on the 27th of June 2014 in Tallinn